Complex Geophysical Solution for Seismohydrogeological Problems of Balneology in Mongolia - Serebrennikov, SP; Dzhurik, VI; Batsaikhan, Ts; Drennov, AF (Proceedings of the Mongolian Academy of Sciences, 2011)
The present paper is concerned with geophysical trends of particular importance to organizing, planning and building resorts in Mongolia. The possibilities for integrated geophysical and engineering-seismological investigations have been demonstrated with the resort construction site near Ulaanbaatar town. The investigations have resulted in obtaining thickness of loose deposits, depth of groundwater occurrence, and estimates of relative seismic hazard and soil conditions. Two aquifers have been presumably identified and parameters of seismic effects have been estimated for expectable earthquakes as applied to two potential levels of initial seismic activity in Ulaanbaatar town. This provides an example of the possibility of finding complex solution to seismohydrogeological problems of balneology in seismically active areas throughout Mongolia. DOI: http://dx.doi.org/10.5564/pmas.v0i4.44 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.32-41